Investigation of Anaplasma Species with Veterinary and Public Health Significance in Sheep and Goats - Karatepe, Mustafa; Aktas, Munir; Karatepe, Bilge; Ozubek, Sezayi (Springer Int Publ Ag, 2025)
PurposeThis study was carried out to investigate Anaplasma important for veterinary and public health in sheep and goats in Ni & gbreve;de province in T & uuml;rkiye by using molecular methods.MethodsBlood samples were taken from randomly selected 690 animals (520 sheep and 170 goats), which were between 1 and 10 years old and from different study sites in Ni & gbreve;de by using the vacutainer tubes containing EDTA. After the genomic DNA extractions samples, the Anaplasma spp. 16S rRNA genes were amplified by PCR. Species-specific polymerase chain reaction (PCR) assays were performed on positive samples for the presence of A. bovis, A. capra, A. ovis, A. platys-like, and A. phagocytophilum. At the same time, the animals were tested for ixodid tick infestation and collected ticks were examined for identification under the stereo-microscope.ResultsThe results of PCR analysis show that the overall A. ovis prevalence was 63.3% (437/690) in small ruminants sampled. A total of 361 sheep (69.4%) and 76 goats (44.7%) were found to be infected with A. ovis, whereas no positivity was detected for A. bovis, A. capra, A. platys-like, and A. phagocytophilum. Anaplasma ovis positivity was observed at the highest percent in May (%74.6) while the lowest in June (%52.4). In total, 1361 ticks (579 female, 782 male) were collected from sheep and goats in Ni & gbreve;de. Ticks were identified as Rhipicephalus bursa (383, 28.1%), R. turanicus (607, 44.6%), Hyalomma marginatum (7, 0.5%), Hy. excavatum (247, 18.1%), Hy. anatolicum (23, 1.7%), Haemophsalis parva (21, 1.5%), Hae. punctata (7, 0.5%), Hae. sulcata (40, 2.9%) and Dermacentor marginatus (26, 1.9%).ConclusionThe present study reports a high prevalence of A. ovis 63.3% (437/690) in sheep and goats in Ni & gbreve;de province.
Keywords: Sheep; Goat; Anaplasma; Tick